Gambaran Tingkat Kepuasan Layanan Pasien BPJS Di Klinik Pratama Santa Elisabeth Medan Tahun 2023 - Samfriati Sinurat; Jagentar Perlindungan Pane; Juwita Br. Siahaan (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Satisfaction is an indicator used in determining the standard of a health facility. The quality of a service is closely related to customer satisfaction, this happens because service quality can create a good relationship between consumers and an agency, in the long run this relationship can make agencies understand how to meet consumer needs. The purpose of this study was to describe the level of satisfaction with BPJS patients' health services at Primary clinics in 2023. This research is descriptive in nature, with a cross-sectional design. The research population is unknown where a sample of 45 people, and taken based on purposive sampling techniques. Data collection was carried out directly to respondents using interview techniques. The results showed that the satisfaction level of Primary clinic users was very satisfied by 62.2%, satisfied by 20.0% while quite satisfied by 2.2% was dissatisfied15.6 It is hoped that the Primary clinic can further improve the quality of service quality by providing enough doctor time and nurses serving patients.